Liver Biopsy and Pressure Hemodynamics: GI Perspective - Kesar, Varun; Kesar, Vivek; Monkemuller, Klaus; Yeaton, Paul (Digestive Disease Interventions, 2023)
Endoscopic ultrasound (EUS) has come a long way from mere diagnostic modality to performing interventional procedures like fine needle aspiration, gastric varices glue and coiling, and management of pancreatic fluid collection along with necrosectomy. Recently, EUS-guided biopsy of the liver has gained traction. This coupled with the ability to access the portal vein and measure portal pressure has made comprehensive liver evaluation possible using endoscopic route. In this review, we will discuss evolution and techniques of performing EUS-guided liver biopsy and portal pressure gradient. We will also compare the merits and demerits as compared with the other conventional techniques.
Keywords: endosonography; endoscopy; fine needle aspiration; fine needle biopsy; portal pressure gradient; hepatic venous portal gradient; liver biopsy